2021
DOI: 10.3389/fcimb.2021.681518
|View full text |Cite
|
Sign up to set email alerts
|

Transition From PCR-Ribotyping to Whole Genome Sequencing Based Typing of Clostridioides difficile

Abstract: Clostridioides difficile causes nosocomial outbreaks which can lead to severe and even life-threatening colitis. Rapid molecular diagnostic tests allow the identification of toxin-producing, potentially hypervirulent strains, which is critical for patient management and infection control. PCR-ribotyping has been used for decades as the reference standard to investigate transmission in suspected outbreaks. However, the introduction of whole genome sequencing (WGS) for molecular epidemiology provides a realistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Although PCR-ribotyping is the gold-standard method for genotyping, it does not provide sufficient discriminatory power to distinguish related strains. 32 Furthermore, it suggests that there was no epidemiologic transmission of C. difficile ST-37/RT017 strains between the departments in our hospital during this period. Comparing the same clones of C. difficile ST-37/RT017 strains isolated from the neurosurgery department, we found that there was no transmission of C. difficile ST-37/RT017 strains on the same floor, as the strains apparently derived from different clones.…”
Section: Discussionmentioning
confidence: 79%
“…Although PCR-ribotyping is the gold-standard method for genotyping, it does not provide sufficient discriminatory power to distinguish related strains. 32 Furthermore, it suggests that there was no epidemiologic transmission of C. difficile ST-37/RT017 strains between the departments in our hospital during this period. Comparing the same clones of C. difficile ST-37/RT017 strains isolated from the neurosurgery department, we found that there was no transmission of C. difficile ST-37/RT017 strains on the same floor, as the strains apparently derived from different clones.…”
Section: Discussionmentioning
confidence: 79%
“…These data demonstrate that C. difficile ribotype 151 is polyphyletic with isolates from the same ribotype falling into two different cryptic clades as well as a 'regular' clade, which has not been reported before. Though there is good concordance between PCR ribotype and MLST-based approaches (13,35,36), these findings underscore that PCR ribotyping is insufficiently discriminatory for phylogenetic placement.…”
Section: Core Genome Phylogeny Places Some Rt151 Isolates In Cryptic ...mentioning
confidence: 94%
“…Tigecycline, a glycylcycline chemically and structurally similar to tetracyclines, has been proposed for the treatment of CDI due to its ability to inhibit spore formation and reduce the toxin production by the pathogen [ 80 ]. It should be noted that some tet genes (i.e., tet (X3) and tet (X4), encoding a flavin-dependent monooxygenase), which [ 81 , 82 , 83 , 84 , 85 , 86 , 87 ] typically confer tetracycline resistance, also appear to mediate tigecycline resistance in various microorganisms of clinical relevance [ 81 , 82 ], thus challenging the clinical efficacy of the entire family of tetracycline antibiotics, including any derivatives.…”
Section: Antimicrobial Resistance Genesmentioning
confidence: 99%
“…Due to its high discrimination capacity, PCR ribotyping is currently recommended by the European Centre for Disease Prevention and Control (ECDC) for surveillance of the C. difficile spread [ 84 ]. However, this molecular technique has a delivery time of up to one week and often requires in-house protocol optimization, thus not being fully transferable between laboratories [ 85 ]. Another technique in use is pulsed-field gel electrophoresis (PFGE).…”
Section: Molecular Typing Techniques For C Difficile ...mentioning
confidence: 99%
See 1 more Smart Citation